Microfoundations of Strategic Leadership in Encouraging Adaptive Educational Personnel Performance: The Mediating Role of Psychological Empowerment in Private University - Kuswinton; Misran; Resfika Aswira; Risna; Yusman Sutoyo (Fundamental and Applied Management Journal, 2026)
This study aims to analyze the influence of strategic leadership microfoundations on the adaptive performance of educational staff, with the mediating role of psychological empowerment in private higher education institutions. This research is motivated by the increasing demands for adaptation in higher education organizations amidst digital disruption, changes in the work environment, and increasingly complex academic service dynamics. Unlike previous studies that emphasize strategic leadership at the macro-organizational level, this study uses a microfoundations perspective to explain how strategic leadership works through individual psychological mechanisms in shaping employee adaptive behavior. The study used a quantitative approach with a survey method of 171 educational staff at several private universities. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that strategic leadership microfoundations had a positive and significant effect on psychological empowerment. However, the direct effect of strategic leadership on adaptive performance was not significant. These findings indicate that adaptive performance is not formed directly through the leader's strategic vision and control, but through individual psychological processes that create a sense of competence, autonomy, work meaning, and influence within the organization. Furthermore, psychological empowerment was shown to play a key role in explaining how strategic leadership translates into adaptive behavior in educational staff. This study provides theoretical contributions by expanding the literature on microfoundations, strategic leadership, and employee adaptability, and confirms that the adaptive capacity of higher education organizations is rooted in individual psychological dynamics at the micro level.